Electrochemical Upgrading of Bio-Oil. (30th May 2017) - Elangovan, S; Larsen, Dennis; Bay, Insoo; Mitchell, Evan; Hartvigsen, Joseph; Millett, Byron; Elwell, Jessica; Santosa, Daniel; Elliott, Douglas C
Abstract : Bio-oil produced by fast pyrolysis of biomass is a potential source of low carbon, renewable hydrocarbon fuel. However, the properties such as low heating value, incomplete volatility, acidity, instability, and incompatibility with standard fuels restrict its use. The undesirable properties of pyrolysis oil result from its chemical composition that mostly consists of different classes of oxygenated organic compounds. Current process of Hydrodeoxygenation to remove oxygen involves high-temperature, high-pressure processing in the presence of hydrogen and catalyst. An alternative process of deoxygenation of bio-oil using solid-state, oxygen conductor based electrochemical cell is under investigation. The electrolysis process removes oxygen from the oxygenated organic molecule as well from steam to produce hydrogen in-situ allowing for a distributed, small scale integrated upgrading unit. Mixtures of model compounds and a slip stream of pyrolysis vapor were tested. The results show the potential for integrating a pyrolyzer and an electrochemical device for stabilizing pyrolysis oil.